Probiotic Effects of Bacillus licheniformis DSM5749 on Growth Performance and Intestinal Microecological Balance of Laying Hens - Pan, Xue; Cai, Yuanli; Kong, Linglian; Xiao, Chuanpi; Zhu, Qidong; Song, Zhigang (Frontiers in Nutrition, 2022)
This study was conducted to investigate the impact of Bacillus licheniformis DSM5749 on the production performance and intestinal health in laying hens. A total of 540 32-week-old laying hens (Hyline Brown) were randomly allocated to two dietary groups (10 replicates of 27 laying hens), namely, basal diet and basal diet complemented with 200 g/t B. licheniformis (3.2×109 cfu/t). The trial lasted for 8 weeks, and samples were collected at the last week. Results revealed that B. licheniformis DSM5749 significantly improved the laying performance, including an increase in egg production rate, average daily egg yield and decrease of feed-to-egg ratio during the entire 8-week experiment period (P < 0.05). B. licheniformis DSM5749 increased the level of superoxide dismutase and glutathione peroxidase in the liver and IL-1 level in the serum (P < 0.05). In addition, the integrity of intestinal morphology (Villus height, Crypt depth, and Villus height/Crypt depth) and tight junction (ZO-1 ,Claudin-1 and Occludin), and the secretion of lipase vitality in the intestine were potentiated by B. licheniformis DSM5749 in laying hens (P < 0.05). Firmicutes/Bacteroidetes ratio decreased (P < 0.05) after B. licheniformis DSM5749 were administered. Further, B. licheniformis DSM5749 modulated the composition of the cecal microbiota of the laying hens, increasing the relative level of beneficial bacteria at the genus level (e.g., Prevotella) and decreasing the level of potential pathogens (e.g., Desulfovibrio ). In conclusion, B. licheniformis DSM5749 can improve the laying performance of laying hens, promote intestinal health, affect the composition of cecal microorganisms, and regulate the intestinal micro-ecological balance, making B. licheniformis a good probiotic candidate for application in the laying hens industry.